Media and Religion: Da'wah on the Role of Teachers on the Muhammadiyah Website : Media dan Agama: Dakwah Peran Guru di Website Muhammadiyah - Rodiyah, Nuning; Rachman, Rio Febriannur (Dakwatuna: Jurnal Dakwah dan Komunikasi Islam, 2026)
This study examines how Muhammadiyah, one of Indonesia’s largest Islamic organizations, utilizes its official website as a medium of digital da’wah and educational communication, with a particular focus on the portrayal of teachers as moral and intellectual agents. Using a qualitative content analysis of selected articles published on muhammadiyah.or.id, the research explores how religious narratives are integrated into discourses of pedagogy, professionalism, and moral ethics. Drawing upon Gary R. Bunt’s theory of the Cyber Islamic Environment (CIE) and Everett Rogers’ Diffusion of Innovation, the study situates Muhammadiyah’s online activities within the broader framework of technological mediation and religious reform (tajdid). Findings reveal that the website functions not only as an informational platform but also as a transformative arena of moral communication, where teachers are depicted as digital missionaries embodying Islamic values through educational praxis. The research underscores that Muhammadiyah’s digital da’wah represents a shift from one-way religious dissemination to participatory moral education, fostering the emergence of ethical digital citizenship in contemporary Islamic education.